2019
DOI: 10.1002/adma.201805717
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering and Surface Functionalization of Nanocarbons for Metal‐Free Catalysis

Abstract: With the advent of carbon nanotechnology, which initiated significant research efforts more than two decades ago, novel materials for energy harvesting and storage have emerged at an amazing pace. Nevertheless, some fundamental applications are still dominated by traditional materials, and it is especially evident in the case of catalysis -and environmentalrelated electrochemical reactions, where precious metals such as Pt and Ir have been widely used. Several strategies have been recently explored for achievi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(100 citation statements)
references
References 106 publications
0
100
0
Order By: Relevance
“…Due to the similar bond length of CC and CN, N doping in graphene layers can occur with minimal distortion of the carbon structure. Significant effort has been devoted toward finding out what type of nitrogen (pyridinic, pyrrolic, graphitic, or oxidized) is responsible for the active site in N‐doped carbons for ORR, without consensus to date . Some studies suggest that pyridinic N is the active site for ORR, via creation of Lewis basic sites and subsequent activation of the neighbor carbon .…”
Section: Heteroatom Doping Defects and Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the similar bond length of CC and CN, N doping in graphene layers can occur with minimal distortion of the carbon structure. Significant effort has been devoted toward finding out what type of nitrogen (pyridinic, pyrrolic, graphitic, or oxidized) is responsible for the active site in N‐doped carbons for ORR, without consensus to date . Some studies suggest that pyridinic N is the active site for ORR, via creation of Lewis basic sites and subsequent activation of the neighbor carbon .…”
Section: Heteroatom Doping Defects and Hybridizationmentioning
confidence: 99%
“…Significant effort has been devoted toward finding out what type of nitrogen (pyridinic, pyrrolic, graphitic, or oxidized) is responsible for the active site in N‐doped carbons for ORR, without consensus to date . Some studies suggest that pyridinic N is the active site for ORR, via creation of Lewis basic sites and subsequent activation of the neighbor carbon . Other works indicated that graphitic N is the one promoting the activity, instead .…”
Section: Heteroatom Doping Defects and Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The large degree of disorder and nonuniform, packing of (002) domains leaves more vacant space in the CNF interior. This is significant because the irregularity results in an increased number of defects and can lead to additional active sites for catalysis 51,52 . This morphology also gives access to a larger accessible surface area for gas Treatment at 1050°C leads to the formation of metal nanoparticles assembled on carbon nanofibers which have been demonstrated to have enhanced electrocatalytic activity, gas sensing performance, and lithium storage 1, 22,55,56 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Through electrode modifiers, metal free composites with electrocatalytic activity are very promising because of their high durability, lack of impurity poisoning, being environment friendly and commercialization capability [18]. These electrocatalysts are generally prepared by doping heteroatoms such as nitrogen, oxygen, phosphorus and sulfur into carbon nanostructures or physically and chemically functionalizing their surface with various functional groups and subsequently are widely used in energy conversion and storage devices and electrochemical sensors [19][20][21]. For instance Li et al introduced a novel N-doped graphene quantum dots decorated N-doped carbon nanofibers composite to determine nitrite ions present in sausage, pickle, lake water and tap water [22].…”
Section: Introductionmentioning
confidence: 99%